14.MOLECULAR DETECTION OF CYTOMEGALOVIRUS IN A SAMPLE OF IRAQI PATIENTS WITH ACUTE LEUKEMIA AND STEM CELL TRANSPLANTATION (Iraqi Journal of Medical Sciences, 2018)
Background: Acute leukemia and hematopoietic stem cell transplantation are risk factors for opportunistic infection and reactivation of many latent infection like cytomegalovirus.Objective: Detection and quantification of cytomegalovirus viremia in patients with acute leukemia after induction chemotherapy and post allogeneic stem cell transplantation patients.Methods: A prospective study enrolled 61 patients with acute leukemia. Forty-eight of them evaluated while induction chemotherapy (group I), while the other 13 within 1-year post bone marrow transplantation (BMT) (group II). In addition, 30 apparently healthy individuals were recruited as (control group), blood samples were collected from all groups. Viral DNA was extracted from 1 ml plasma samples, and then, cytomegalovirus DNA was detected and quantitatively assessed by Taqman quantitative real-time PCR.Results: Twelve (25%) out of 48 patients in group I, 2 (15.4%) out of the 13 patients in group II, and 2 (6.7%) out of 30 in the control group had positive cytomegalovirus viremia. The mean cytomegalovirus viremia was 5.192x102, 2.71x102 and 1.60x102 copies/ml for group I, group II and controls respectively, p=0.056. Conclusion: There is a relatively high prevalence of cytomegalovirus viremia in Iraqi patients with acute leukemia after chemotherapy and post BMT. Real-time PCR assay is helpful for early diagnosis of cytomegalovirus viremia in leukemic patients and used to monitor post BMT patients at risk for cytomegalovirus disease.Keywords: HCMV, acute leukemia, stem cell transplantation, real-time PCRCitation: Al-Toban HA, Al-Marsomy HD, Al-Obaidi AB, Al Tameemi WF, Mohammed MA, Al-Saeed RM, Al-Shemary IK. Molecular detection of cytomegalovirus in a sample of iraqi patients with acute leukemia and stem cell transplantation. Iraqi JMS. 2018; 16(3): 344-352. doi: 10.22578/IJMS.16.3.14
Keywords: HCMV; acute leukemia; stem cell transplantation; realtime PCR